Radial Column Excision and Four-Corner Fusion for the Treatment of Basal Thumb Arthritis and Scapholunate Advanced Collapse Wrist or Midcarpal Arthritis - Mandaleson, Avanthi; Wagels, Michael; Tham, Stephen K. (Journal of Wrist Surgery, 2017)
Background The combination of trapeziometacarpal arthritis and intercarpal pattern of degenerative wrist arthritis is uncommon.Purpose To report on the clinical and radiologic results of patients who have undergone radial column excision (scaphoidectomy and trapeziectomy) (RCE) and four-corner fusion (4CF). We describe the patterns of disease that present with basal thumb and midcarpal arthritis and treatment outcomes of a single-surgeon series.Patients and Methods A consecutive series of seven patients underwent RCE and 4CF over a 2-year period, for basal thumb osteoarthritis with concurrent degenerative midcarpal wrist arthritis. Six patients were available for review. All six patients were women with a mean age of 73 years (range: 67–78; SD 4.6). Mean follow-up time was 48.2 months (34–59 months). Radiographic and clinical outcomes were recorded for all patients, to include wrist range of motion, key pinch, grip strength, and patient-rated wrist evaluation (PRWE).Results There were no failures or revision procedures. The mean range of motion was flexion of 40 degrees (range: 30–40 degrees), extension of 30 degrees (range: 20–42 degrees), radial deviation of 18 degrees (range: 10–30 degrees), and ulnar deviation of 15 degrees (range: 0–25 degrees). The mean key pinch was 4.2 kg (range: 0.5–10, SD ± 3.5) and mean grip strength was 9.4 kg (range: 0–19, SD ± 8.9). The PRWE results in four patients were within normal values.Conclusion RCE with 4CF resulted in acceptable clinical outcomes in four of six patients treated, with no failures at a mean follow-up of 48.2 months.Level of Evidence Level IV, therapeutic study.
Keywords: basal thumb arthritis; four-corner fusion; limited wrist arthrodesis; partial wrist fusion; midcarpal arthritis; trapeziometacarpal arthritis